What are the challenges that social prescribers face when supporting people within dementia and how can these be addressed? A qualitative study - Claudio Di Lorito; Marie Poole; Greta Rait; Kritika Samsi; Louise McComiskie; Louise Robinson; Jane Wilcock (PLoS ONE, 2025)
Introduction Evidence suggests that social prescribing might have a positive impact on identity, control, creativity and quality of life in people with dementia. While evidence on the benefits of social prescribing is accumulating, there is a sparsity of research on the experiences of social prescribers. This study aims to identify the challenges that social prescribers face when supporting people with dementia and their families and strategies to address these. Materials and methods A qualitative study involving 24 social prescribers from all regions in England. Semi-structured interviews investigated challenges and strategies that social prescribers experience in their own practice. Data were analysed through thematic analysis. Results on “Challenges” and the respective “Strategies” are presented in a chronological order that reflects the different stages of contact with and support for the client with dementia, from referral to discharge. Results and discussion This study identified unique barriers that social prescribers face when working with people with dementia, particularly around communication, motivation, engagement and overdependency. It identified person and system-level strategies that can be used to address these challenges. These include expanding opportunities for dementia training, offering in-person support, including social prescribing in annual dementia reviews, and increasing integration of services within Integrated Care Systems and collaborations between health care service providers and with the third sector. Improving delivery and effectiveness of services is crucial to ensure that social prescribing fulfils its ethos of personalised care approach for all, including people with dementia, as envisioned in the NHS long term plan.